2000
DOI: 10.21273/hortsci.35.1.46
|View full text |Cite
|
Sign up to set email alerts
|

High Relative Humidity Increases Yield, Harvest Index, Flowering, and Gynophore Growth of Hydroponically Grown Peanut Plants

Abstract: Growth chamber experiments were conducted to study the physiological and growth response of peanut (Arachis hypogaea L.) to 50% and 85% relative humidity (RH). The objective was to determine the effects of RH on pod and seed yield, harvest index, and flowering of peanut grown by the nutrient film technique (NFT). `Georgia Red' peanut plants (14 days old) were planted into growth channels (0.15 × 0.15 × 1.2 m). Plants were spaced 25 cm apart with 15 cm between channels. A modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Namely, the higher the accumulated N in leaves, the lower the ear weight. This result corresponds to a previous study, which showed that higher relative humidity produces heavier leaf fresh weight and larger leaf area [34]. Another study showed that excising the uppermost two leaves promoted N remobilization from vegetative organs to kernels on maize [35].…”
Section: Correlation Analysis Among Climate Variables Soil Properties...supporting
confidence: 91%
See 1 more Smart Citation
“…Namely, the higher the accumulated N in leaves, the lower the ear weight. This result corresponds to a previous study, which showed that higher relative humidity produces heavier leaf fresh weight and larger leaf area [34]. Another study showed that excising the uppermost two leaves promoted N remobilization from vegetative organs to kernels on maize [35].…”
Section: Correlation Analysis Among Climate Variables Soil Properties...supporting
confidence: 91%
“…One study indicated that high relative humidity facilitated reduced iron deficiency chlorosis symptoms to obtain higher plant dry weight and increasing plant height, when comparing lower (60%) and high (90%) relative humidity effects on iron deficiency chlorosis in soybean [33]. Meanwhile, if adequate nutrition is supplied, high relative humidity also increases yield on peanut [34]. Thus, increase of relative humidity seems beneficial to crops when adequate nutrition is applied.…”
Section: Correlation Analysis Among Climate Variables Soil Properties...mentioning
confidence: 99%
“…In addition, a large body of literature points to even more systemic and complex effects of VPD on plant physiology, particularly on the anatomical, biochemical, and developmental levels, independent from variation in soil moisture. For instance, plants exposed to long‐term VPD increases (over weeks to months) exhibit changes in stomatal density and size (e.g., Fanourakis et al, 2013), leaf venation (e.g., Carins Murphy et al, 2014), internal leaf anatomy (e.g., Leuschner, 2002), shoot architecture and root growth (e.g., Darlington et al, 1997; Ford & Thorne, 1974; Gislerød & Nelson, 1989), biochemical composition (e.g., Aliniaeifard et al, 2014; De Luis et al, 2002), and even the growth rate of reproductive organs (e.g., Mortley et al, 2000; Turc et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Vapour pressure deficit was lower when the relative humidity of the atmosphere was comparatively higher. Crop yield increased with increased relative humidity during middle stage of crop growth (Mortley et al, 2000). During post-flowering phase, biomass production increased with higher relative humidity (Mortley et al, 1994).…”
Section: Air Temperatures During Vegetative Phase Played Positive Rolmentioning
confidence: 98%